Association of Nirmatrelvir/Ritonavir Treatment on Upper Respiratory Severe Acute Respiratory Syndrome Coronavirus 2 Reverse Transcription-Polymerase Chain Reaction (SARS-Cov-2 RT-PCR) Negative Conversion Rates Among High-Risk Patients With Coronavirus Disease 2019 (COVID-19). (19th August 2022) - Li, Hongyan; Gao, Menghan; You, Hailong; Zhang, Peng; Pan, Yuchen; Li, Nan; Qin, Ling; Wang, Heyuan; Li, Dan; Li, Yang; Qiao, Hongmei; Gu, Lina; et al.
Abstract: Background: Acceleration of negative respiratory conversion of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in patients with coronavirus disease 2019 (COVID-19) might reduce viral transmission. Nirmatrelvir/ritonavir is a new antiviral agent recently approved for treatment of COVID-19 that has the potential to facilitate negative conversion. Methods: A cohort of hospitalized adult patients with mild-to-moderate COVID-19 who had a high risk for progression to severe disease were studied. These patients presented with COVID-19 symptoms between 5 March and 5 April 2022. The time from positive to negative upper respiratory reverse transcription-polymerase chain reaction (RT-PCR) conversion was assessed by Kaplan-Meier plots and Cox proportional hazards regression with the adjustment for patients' baseline demographic and clinical characteristics. Results: There were 258 patients treated with nirmatrelvir/ritonavir and 224 nontreated patients who had mild-to-moderate COVID-19. The median (interquartile range) time for patients who converted from positive to negative RT-PCR was 10 days (7–12 days) in patients treated ≤5 days after symptom onset and 17 days (12–21 days) in nontreated patients. The proportions of patients with a negative conversion at day 15 were 89.7% and 42.0% in treated patients and nontreated patients, corresponding to a hazard ratio of 4.33 (95% confidence interval, 3.31–5.65). Adjustment for baseline differences between the groups had little effect on the association. Subgroup analysis on treated patients suggests that time to negative conversion did not vary with the patients' baseline characteristics. Conclusions: This cohort study of high-risk patients with mild-to-moderate COVID-19 found an association between nirmatrelvir/ritonavir treatment and accelerated negative RT-PCR respiratory SARS-CoV-2 conversion that might reduce the risk of viral shedding and disease transmission. Abstract : High-risk patients with mild-to-moderate COVID-19 treated with nirmatrelvir/ritonavir have more rapid negative conversion of nasopharyngeal or oropharyngeal SARS-CoV-2 reverse-transcription polymerase chain reaction positivity that might attenuate viral transmission.